Targeted Motor Rehabilitation Dissociates Corticobulbar Versus Corticospinal Dysfunction in an Animal Model of Parkinson's Disease. (January 2014) - Plowman, Emily K.; Maling, Nicholas; Thomas, Nagheme J.; Fowler, Stephen C.; Kleim, Jeffrey A.
Background. Recent evidence suggests that motor training may be beneficial for slowing the onset of motor impairments in Parkinson's disease (PD). Objective. To examine the impact of targeted rehabilitation on limb motor and cranial motor function and the corresponding corticospinal and corticobulbar circuits in a rodent model of PD. Methods. Baseline performance of limb (reaching) and cranial (licking) motor function were established prior to and 6 weeks following unilateral intrastriatal 6-hydroxydopamine (6-OHDA) infusions. Animals then received 6 weeks of limb motor rehabilitation (LMR) or cranial motor rehabilitation (CMR), after which motor performance was reassessed. Intracortical microstimulation (ICMS) was used to generate motor maps of corresponding corticospinal (forelimb) and corticobulbar (tongue) movement representations within the motor cortex ipsilateral to the 6-OHDA infusion. Quantitative tyrosine hydroxylase (TH) immunohistochemistry was performed to determine levels of striatal TH depletion in 6-OHDA animals using near infrared densitometry. Results. (1) unilateral intrastriatal dopamine depletion impaired both reaching accuracy and lick force; (2) targeted LMR ameliorated impairments in reaching performance; however, CMR did not improve lick force impairments; (3) unilateral dopamine depletion significantly reduced forelimb but not tongue motor map topography; (4) LMR partially restored forelimb motor maps, whereas CMR did not alter tongue motor maps; and (5) significant correlations were observed between skilled reaching accuracy, forelimb motor map area, and TH depletion, but no relationships were revealed for cranial motor function, motor maps, or TH depletion. Conclusions : These data demonstrate dissociation between striatal dopamine depletion, limb versus cranial motor function, and targeted motor rehabilitation in a rodent model of PD.